Phonophoresis Plus Topical Nitroglycerin Versus Hydrocortisone for the Management of Plantar Fasciitis: A Randomized Controlled Trial: - Maghroori, Razieh; Fakhari, Shiva; Taheri, Parisa (Galen Medical Journal, 2021)
Background: Plantar fasciitis (PF), is the most common reason for inferior heel pain. Various approaches have been raised for the treatment of PF; however, none had substantial outcomes. The current study aims to assess and compare phonophoresis outcomes plus topical nitroglycerin versus phonophoresis plus topical hydrocortisone for PF management. Materials and Methods: The current randomized clinical trial was conducted on 65 patients with PF diagnosis, who underwent ten every-other-day treatment sessions with phonophoresis plus 20mg nitroglycerin (n=33) or 20mg hydrocortisone (n=32), respectively. The Modified Roles and Maudsley (RM) score and the visual analog scale (VAS) were compared between the two groups at baseline, three weeks, and two months after the interventions. Besides, the plantar fascia thickness was measured at baseline and two months after the intervention. Results: The baseline RM (P=0.067) and pain severity (P=0.057) was similar between the two groups, but other assessments revealed the superiority of phonophoresis plus topical nitroglycerin over topical hydrocortisone (P<0.05). The reduction in plantar fascia thickness was more in phonophoresis plus nitroglycerin-treated patients as compared to the latter group (P<0.001), but the requirement of additional doses of analgesia was remarkably more in hydrocortisone-treated patients (P<0.001). Conclusion: Based on the current study, phonophoresis plus topical nitroglycerin was superior to phonophoresis plus topical hydrocortisone in pain relief, improved quality of life, and decreased fascia thickness. However, further investigations are required to achieve the ultimate outcomes for a more extended period. [GMJ.2021;10:e2072]